Forensic method to determine gender in sub adult subjects using odontometrics in the deciduous dentition - Rodríguez-Flórez, Carlos David; Mangeaud, Arnaldo; Colantonio, Sonia; Fonseca, Gabriel Mario (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: for many years, anthropological studies of sub-adult contemporary samples suggest that a low sex dimorphism expressed in morphology patterns exist. The objective was to evaluate the sex dimorphism in a sample of sub adults from Cordoba City, Argentina using dental dimensions in deciduous teeth. Methods: this article describes the dental dimorphism in a sample of 98 sub-adults with deciduous dentition from Córdoba City, Argentina. Mesial -distal and buccal-lingual diameters of the deciduous dentition were taken and the data was analyzed with Weighted Boundary (WB) index and multivariate discriminate stepwise analysis. Results and conclusion: an alternative technique for gender determination using the deciduous dentition is proposed. Nine variables that expressed highly significant differences were selected, among them, BL UM1 correctly predicting male gender in 90.9% and female gender in 93.7% of the cases.